Aumolertinib plus bevacizumab for untreated advanced NSCLC with EGFR sensitive mutation - Kong, Lingping; Peng, Lina; Yang, Xue; Ma, Qing; Zhang, Linlin; Liu, Xia; Zhong, Diansheng; Meng, Fanlu (Frontiers in Oncology, 2025)
BackgroundAumolertinib is a novel third-generation epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) with proven efficacy and safety for untreated non-small-cell lung cancer (NSCLC) patients with EGFR sensitizing mutations (EGFRm) in China. The progression-free survival (PFS) improvement of the combination of first-generation EGFR-TKIs and bevacizumab was confirmed by CTONG1509, JO25567, and NEJ026 studies, however, the effect of third-generation EGFR-TKIs plus bevacizumab remains under debate. This study aimed to investigate the efficacy and safety of aumolertinib plus bevacizumab in untreated EGFRm advanced NSCLC.MethodsWe conducted a phase II single-arm prospective clinical trial for advanced EGFRm NSCLC treated with aumolertinib combined with bevacizumab. Treatment continued until disease progression, occurrence of unacceptable toxicities, or the patient withdrew consent. The study was stratified according to sex, smoking history, stage, EGFR mutation status, and central nervous system (CNS) metastasis. The primary endpoint was the 12–month progression-free survival rate (PFS%), and secondary endpoints included the objective response rate (ORR), overall survival (OS), and progression-free survival (PFS).ResultsBetween September 16, 2020, and November 11, 2021, a total of 21 patients were enrolled in the study. The median follow-up was 36.8 months (ranging from 33.2 to 40.4 months), and all 21 patients were included in the evaluation. The PFS% at 12-month was 81% (95% confidence interval (CI): 64.1–97.9%), the median PFS was 26 months (95% CI: 16.5-35.5) and the ORR reached 85.7%, with an average reduction of the target lesions of 48.2%. Among patients with CNS metastasis, the ORR was 92.9% (13/14), and for TP53 co-mutation patients, the ORR was 86.6% (12/14). Grade 3 adverse events were observed in 4 patients (19.2%), and no grade 4 or 5 adverse events reported.ConclusionThe combination of aumolertinib and bevacizumab in patients with advanced EGFRm NSCLC achieved the study’s primary endpoint. This study indeed extended PFS compared with previous literature, and it was deemed safe and tolerable.